Beyond Death Beliefs, Practice, and Material Expression - Williams, Patrick; Feinman, Gary; Muro Ynoñán, Luis Armando (BAR International, 2022)
A wide-ranging treatment on the meaning of death, and its juxtaposition with life, from biological, cultural, and spiritual perspectives. Dozens of case studies accompany the principal essays written by scholars, Indigenous community members, and curators of the exhibition Death: Life's Greatest Mystery. This volume offers a richly illustrated companion to the exhibition, produced by Chicago's Field Museum of Natural History, and contains full page photographs of the stunning objects in the exhibit, most from the Field Museum's collections. This volume is intended to engage visitors to the exhibition and members of the general public who want to delve more fully into questions surrounding death and the multiple religious, historical, and cultural perspectives on it. Although not a comprehensive guide, the book touches on many world religions and case studies drawn from five continents.